BC-g-PAA: Characterization and Establishment of the IPN Hydrogel - Jelita Jelita; Sri Wahyuna Saragih; Wardatul Husna Irham (Jurnal Penelitian Pendidikan IPA, 2024)
A study on the manufacture of bacterial cellulose IPN hydrogel crosslinked poly acrylic acid using the MBA crosslinker. This study aims to characterize and observe the reaction to form bacterial cellulose-based hydrogel IPN. The BC-g-PAA was characterized by the degree of cross-linking, swelling ratio, and FTIR analysis. The results of this study found predictions of the reaction process for the formation of IPN Hydrogel in several process stages, namely 1) The polymerization process of bacterial cellulose chains that form cross-linked networks independently, 2) The process of cross-linking Acrylate monomers with MBA crosslinkers in three steps, i.e. initiation, propagation and termination, 3) Reaction process Formation of IPN network. The results of the characterization test for the degree of crosslinking were 54.55%; Swelling ratio of 1631.25%. FTIR analysis shows that there is a peak that identifies the occurrence of crosslinking